Access to finance and rural youth entrepreneurship in Benin: Is there a gender gap?. (27th January 2022) - Senou, Melain Modeste; Manda, Julius
Abstract: Rural entrepreneurship is an important employment generation intervention for the fast‐growing young labour force in developing countries. Many bottlenecks including access to finance impede rural youths from performing in their new ventures. This paper examines the impact of access to finance on rural youths' entrepreneurship in Benin using data from the second wave of the School‐To‐Work Transition Survey, involving over 900 youths. The paper employs the endogenous switching regression technique, combined with propensity score matching, to investigate the drivers of rural youths' access to finance and its impact on entrepreneurship intention and performance. The results indicate that age, education, poverty status, experience, working in the agricultural sector and the existence of a bank branch are important determinants of rural youths' access to finance. The results also show that access to finance increases the probability of youth entrepreneurship by 15.2% on average. Moreover, the study shows a significant gender gap in rural entrepreneurship of 5.24% among youths with access to finance in Benin. These results suggest that policymakers should facilitate the access of youth, especially young women, to finance by encouraging formal financial institutions to reduce their credit eligibility conditions for those who do not have collateral.